HEPATITIS C VIRUS GENOTYPING IN CHRONIC HEPATITIS C PATIENTS - I. Qattan; V. Emery (European Scientific Journal, ESJ, 2012)
Chronic hepatitis C virus infection is a massive worldwide healthcare burden with estimated costs in the USA alone of over $5 billon per annum. The virus has a 9.5kb positive sense single-stranded RNA genome with striking heterogeneity between isolates, which has led to it being divided into 6 genotypes and more than 50 subtypes and many quasispecies that has been arisen due to the infidelity of the viral polymerase, which lacks of a proofreading function. The virus exists as a range of related but not identical species at the quasispecies. In each infected individual, HCV circulates as a quasispecies in which the population consists of a number of closely related but distinct genetic species. The distribution of the genotype might be influenced by the mode of transmission and racial group. The only current effective treatment is combination therapy with pegylated interferon plus ribavirin (peg-IFNα + RBV) for 24–48 weeks based for genotypes 1 and 4 is 48 weeks, whereas the treatment for genotypes 2 and 3 is completed in 24 weeks. It has proved effective in up to 50% of those infected with HCV genotype 1 and 4 and it varies with other genotypes. HCV genotype is consider to be a clinically important parameter for determining both; the potential response and the duration of treatment.﻿